Gerakan Teroris dalam Masyarakat Islam: Analisis Terhadap Gerakan Jemaah Islamiyah (JI) - Haji Mohd Yusoff, Zulkifli; Mahmud, Fikri (Jurnal Usuluddin, 2005)
The Islamic society have been uproared recently by terrorism activities. Many observers assumed that among the terrorism movements have root causes in the Moslem community theirself. One of the groups were frequently connected with terrorist activities is Jemaah Islamiyah (JI). This article tries to discourse on this group detailly as its origin, ideology, and strategy of struggle, after wards attempts to give the proper estimation to this group has been listed into the terrorist organizations in the Southeast Asia.